Indole-fused benzooxazepines: a new structural class of anticancer agents. (4th January 2017) - Singh, Ashok K; Raj, Vinit; Rai, Amit; Keshari, Amit K; Saha, Sudipta
Aim: A new series of compounds (1a–16a ) bearing indole-fused benzooxazepine was synthesized, characterized and evaluated for anticancer activity.Materials & methods: In this study, all the synthesized compounds were screened via in vitro anticancer testing on Hep-G2 cancer cell line. A computational study was carried out on cancer-related targets including IL-2, IL-6, COX-2 Caspase-3 and Caspase-8.Results: Some of the synthesized compounds effectively controlled the growth of cancerous cells.Conclusion: The most active compounds –6a, 10a, 13a, 14a and15a – exemplify notable anticancer profile with GI50 <10 μg/ml. Preliminary structure–activity relationship among the tested compounds can produce an assumption that the electronegative groups at phenyl ring attached with indole-fused benzooxazepine are instrumental for the activity. Molecular docking study showed crucial hydrogen bond and π–π stacking interactions, with good ADMET profiling and molecular dynamic simulation. Lay abstract: Indole, azepine and six-membered flexible rings are getting much attention for cancer drug discovery. To contribute to the development of drugs for liver cancer, we designed a new structural class of compounds, indole-fused benzooxazepines. All the compounds were subjected to a preliminary bioassay analysis against Hep-G2 cancer cell line to determine their effect. Studies were also performed on various cancer-related targets to understand the mechanism of action. Our findings show that five compounds were of remarkable efficacy and warrant further investigation. Graphical Abstract: